Influencia del turismo en el crecimiento económico de América Latina periodo 1995-2019 utilizando técnicas de datos panel - Catota Sisalima, Jefferson Rodrigo (2022)
The problem of low economic growth generates concern among those responsible for the preparation of public policy and development researchers, becoming a central concern of the countries, since low economic growth has repercussions at the social and economic level, affecting the structure productive of a country. Therefore, the objective of this research is to determine the impact of tourism on the economic growth of Latin America during the period 1995-2019. Data collected from the World Bank database (2021) and The Heritage Foundation (2021) were used for its implementation. The methodology uses a model of Generalized Least Squares (GLS), cointegration techniques to determine the short-term and long-term equilibrium relationship, and a causality test. The results indicate a positive relationship between tourism and economic growth, as well as a positive relationship between independent and control variables with respect to economic growth. In addition, it was found that there is a short-term and long-term balance between tourism and economic growth. And it is proven that there is no causality between tourism and economic growth. For this reason, it is recommended that governments should diversify the sector through public spending, a new fiscal and financial incentive should be developed, training should be provided on tourism issues and it is proposed to create a department for the investigation of corrupt practices.